Midcarpal Ultra-wide Scapholunotriquetral Capsulo-ligamentoplasty (MUSCL) Procedure - Houghton, Eleanor Ruth; Sivakumar, Brahman; Thompson, Nina; Smith, Nicholas Charles (Journal of Wrist Surgery, 2025)
Arthroscopic dorsal capsuloligamentous reconstruction (ADCLR) has gained popularity in addressing symptomatic scapholunate instability without radiographic malalignment (European Wrist Arthroscopy Society [EWAS] grade IIIB/IIIC/IV).A midcarpal ultra-wide version of the ADCLR is described, wherein suture needles are directly inserted into the midcarpal joint without prior entry into the radiocarpal joint. A wide “bite” is taken to plicate the dorsal radiocarpal (DRC), dorsal intercarpal (DIC), and dorsal scapholunotriquetral (DSLT) ligaments. An incision is then performed to allow direct visualization suture passage beneath the extensor tendons. A total of 68 consecutive patients received a midcarpal ultra-wide scapholunotriquetral capsulo-ligamentoplasty (MUSCL) between July 2020 and November 2023. Mean follow-up was 8 months (range 2–24 months). The mean pre- and postoperative range of dorsiflexion was 64.54 and 68.32 degrees, respectively (p = 0.14). The mean preoperative and postoperative range of palmarflexion was 71.89 and 67.18 degrees, respectively (p = 0.18). A significant improvement of 35.19 points was noted in mean QuickDASH score post-surgery (p < 0.001).Several modifications of the ADCLR exist, including those that take a wider bite incorporating capsule from the mid-carpal joint as well as augmentations with capsuloligamentous imbrications and suture anchor repairs. These approaches yield good pain relief, improved range of motion, and enhanced grip strength when compared with open techniques.This technique eliminates the challenging maneuver of passing needles from the radiocarpal joint into the midcarpal joint, offering both procedural simplicity and efficacy, with promising short-term outcomes. Long-term follow-up is necessary.
Keywords: scapholunate instability; ADCLR; MUSCL; midcarpal ultra-wide scapholunotriquetral capsulo-ligamentoplasty; arthroscopic dorsal capsuloligamentous reconstruction